Guinea [In West African agriculture and climate change: A comprehensive analysis] - Condé, Sidafa; Jalloh, Abdulai; Nelson, Gerald C.; Thomas, Timothy S. (International Food Policy Research Institute, 2013)
The Republic of Guinea covers an area of 245,857 square kilometers divided into seven administrative regions: Kindia, Boké, Mamou, Labé, Faranah, Kankan, and N’Zérékoré. The country consists of four major agroecological regions: coastal (Lower Guinea), middle (Fouta Djallon), upper, and forest Guinea. Guinea has a tropical climate with two alternating seasons, a dry season from November through March and a rainy season from April through October. In general, its rainfall increases from north to south; the mean annual rainfall is 1988 millimeters. Rice is the staple crop, grown on 80 percent of the farms in the country. Rice is cultivated in the upland as well as various lowland ecologies, including inland valley swamps, mangrove swamps, and flooded plains. Other important foodcrops grown and consumed in Guinea are corn, fonio (cultivated grains belonging to the genera Digitaria exilis and Digitaria iburua), groundnuts, and cassava. Exclusively rainfed agriculture is practiced in Guinea, and crop production is significantly influenced by the weather—a growing challenge for resource-poor farmers. The major constraints faced by rice farmers are drought, weeds, and poor soils.